OP0150 MONOCYTE AND MACROPHAGE TRANSCRIPTIONAL PHENOTYPES IN SYSTEMIC JUVENILE IDIOPATHIC ARTHRITIS REVEAL TRIM8 AS A MEDIATOR OF IFNGAMMA HYPERRESPONSIVENESS AND RISK FOR MACROPHAGE ACTIVATION SYNDROME. (June 2019) - Schulert, Grant; Do, Thuy; Dhakal, Sanjeev; Fall, Ndate; Medvedovich, Mario; Salomonis, Nathan; Grom, Alexei
Abstract : Background: Systemic juvenile idiopathic arthritis (SJIA) is a severe and distinct subtype of childhood arthritis. Children with SJIA are at risk for macrophage activation syndrome (MAS), a life-threatening episode of hyperinflammation driven by interferon-gamma (IFNγ). Previous work has suggested that monocytes in SJIA display hyperrsponsiveness to IFNγ, but the molecular basis of this remains unclear. Objectives: Utilize transcriptional profiling of monocytes and macrophages in SJIA to identify polarization phenotypes including features of interferon response Methods: Bulk RNA-sequencing (RNA-seq) was performed on purified monocytes from 26 patients with SJIA without over MAS. In addition, single-cell RNA-seq was performed on isolated bone marrow macrophages from control patients and patients with SJIA and MAS. THP-1 monocytic cells and primary human monocyte-derived macrophages (MDM) were transfected with TRIM8-specific or negative control small-interfering RNA prior to stimulation with IFNγ. Results: RNA-seq of purified SJIA monocytes revealed marked transcriptional changes between cells from patients with high vs low serum ferritin levels. Pathway analysis demonstrated enriched upregulated gene ontology pathways including Response to External Stimulus (p=2.73x10 -17 ), Defense Response (p=2.66x10 -14 ) and Inflammatory Response (p=1.95x10 -11 ). When comparing the SJIA monocyte signature to well-characterized polarization phenotypes, we identified substantial overlap with multiple polarization states, most notably M1 and M2b, but little evidence of IFNγ-induced signature. Among the most highly upregulated genes in SJIA monocytes was tripartite motif containing 8 (TRIM8), an E3 ubiquitin-ligase involved in activation of IFNγ through promoting degradation of the suppressor of cytokine signaling 1 (SOCS1). Elevated TRIM8 expression was found in monocytes from both active and inactive SJIA patients, with the highest levels in those with subclinical MAS features (n=3). Furthermore, we utilized single cell RNA-seq to determine gene expression profiles of bone marrow macrophages from a patient with subclinical MAS. This identified a distinct subpopulation of bone marrow macrophages which exhibited markedly altered transcriptional profiles, with alterations in gene pathways predicted for hemophagocytes in MAS, including cellular response to interferon gamma (p=1.35e-14), endocytic vesicle membranes (p=8.44E-14), and phagosome (p=2.98e-9). These bone marrow macrophage also showed significantly increased TRIM8 expression (6.4-fold increase, p=0.02). To confirm the role of TRIM8 in augmenting macrophage responses to IFNγ, RNA interference was use to knock-down TRIM8 expression in THP-1 cells and MDM. TRIM8 knock-down macrophages showed significant reductions in both early (4 hour) and late (24-48 hours) response to IFNγ, as determined by production of CXCL9, a biomarker for MAS activity in both humans and animal models. Conclusion: Peripheral blood monocytes in SJIA display markers of multiple polarization states, while during MAS tissue macrophages demonstrate a clear IFNγ response phenotype. TRIM8 is highly expressed in both monocytes and macrophages in SJIA, and in vitro knockdown of TRIM8 impairs IFNγ responses in macrophages. Together these data provide a molecular mechanism for monocyte hyperresponsiveness to IFNγ in SJIA, as well as a novel therapeutic target for MAS. Disclosure of Interests: Grant Schulert: None declared, Thuy Do: None declared, Sanjeev Dhakal: None declared, Ndate Fall: None declared, Mario Medvedovich: None declared, Nathan Salomonis: None declared, Alexei Grom Grant/research support from: Novartis, AB2Bio, Novimmune, Consultant for: Novartis